2017
DOI: 10.1111/acer.13513
|View full text |Cite
|
Sign up to set email alerts
|

CREB Protein Mediates Alcohol‐Induced Circadian Disruption and Intestinal Permeability

Abstract: Background Alcoholic Liver Disease (ALD) is commonly associated with intestinal permeability. An unanswered question is why only a subset of heavy alcohol drinkers develop endotoxemia. Recent studies suggest that circadian disruption is the susceptibility factor for alcohol-induced gut leakiness to endotoxins. The circadian protein PER2 is increased after exposure to alcohol and siRNA knockdown of PER2 in vitro blocks alcohol-induced intestinal barrier dysfunction. We have shown that blocking CYP2E1 (i.e., imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
0
8
0
1
Order By: Relevance
“…Ethanol, through multiple mechanisms, is also able to increase the permeability of the intestinal barrier (often referred to as “leaky gut”) that allows further LPS penetration and exposure [ 62 , 118 ]. Oxidative stress from the CYP2E1 metabolism of ethanol could increase intestinal permeability [ 119 , 120 ]. We have shown that, in a Caco-2 cell model, increased oxidative stress leads to increased CREB phosphorylation [ 119 ].…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Ethanol, through multiple mechanisms, is also able to increase the permeability of the intestinal barrier (often referred to as “leaky gut”) that allows further LPS penetration and exposure [ 62 , 118 ]. Oxidative stress from the CYP2E1 metabolism of ethanol could increase intestinal permeability [ 119 , 120 ]. We have shown that, in a Caco-2 cell model, increased oxidative stress leads to increased CREB phosphorylation [ 119 ].…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
“…Oxidative stress from the CYP2E1 metabolism of ethanol could increase intestinal permeability [ 119 , 120 ]. We have shown that, in a Caco-2 cell model, increased oxidative stress leads to increased CREB phosphorylation [ 119 ]. This CREB phosphorylation increases hyperpermeability, most likely, through increased ROS production, which can directly affect the barrier’s integrity [ 5 ].…”
Section: The Tumor Microenvironmentmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 A study on Caco-2 cells showed that alcohol exposure increased oxidative stress and caused monolayer dysfunction, as measured by reduced transepithelial resistance as well as an increase in the levels of circadian clock proteins PER2 and CLOCK. 36 These effects were not seen when the monolayers were pre-treated with an antioxidant scavenger.…”
Section: Mechanisms Of Damage To Gut Barrier In Arldmentioning
confidence: 99%
“…Однако существуют и достаточно убедительные прямые доказательства индукции стволовости в ответ на оксидативный стресс [77][78][79]. Мы нашли доказательства активирующего действия оксидативного стресса для 34 генов из нашего списка: Abca1 [80], Acpp [81], Aldh1a1 [82], Alox15 [83], Arg2 [84], Blnk [46], Ccr3 [85], Cd200 [86], Cd55 [87], Col3a1 [88], Comp [89], Cp [90], Eef1a2 [91], Fgfr1 [92], Gas6 [93], Gstm3 [94], Igf1 [95], Igf2 [96], Il10 [97], Lyve1 [95], Mmp2 [98], Nfatc2 [99], Pde4d [100], Pdk4 [101], Per2 [102], Pon1 [103], Prg4 [104], Rragd [105], Selp [106], Serpinb1a [107], Serpinb2 [108,109], Slc2a4 [110], Tal1 [111], Wnt5a [112].…”
Section: индукция «генов стволовости» в условиях генерализованного клunclassified